Solar Cell System Design for Mechanical Cooling System on the Ferry 500 GT - Shariman, Mustafa; Faturachman, Danny; Dewanto, Yoseph Arya; Muslim, Muswar (International Scientific Academy of Engineering & Technology (ISAET), 2014)
Nowadays energy electricity is a primary need for almost the entire human race. Electrical Energy is very instrumental in carrying out the activities of the economy. Source of electric energy can be produced from a variety of sources of energy. Outline his energy can be in for two kinds of energy that can be updated and energy that cannot be updated. Source of energy that cannot be updated, among others derived from fossil and nuclear and energy can still be updated, among others derived from geothermal (solar energy), ocean waves, waterfalls, wind, etc. Source of energy that cannot be updated, notably energy derived from fossil gradually going on leave because the price become more expensive and the amount of energy sources already reduced. The Energy of the Sun can be used in the energy to heat (solar thermal) or as energy electricity (photovoltaic). Utilization of solar energy as solar photovoltaic plant in the engineering as a source of electrical energy to produce no pollution, air pollution and pollution on the surrounding environment. The basic ingredients of photovoltaic is solar cell. The use of solar cell on a vessel can be used as energy in a variety of electrical equipment on the ship, due to the relative abundance of Sun energy and never run out because the Sun bathes the territory Indonesia 10-12 hours a day. In this case the solar cell used to meet the needs of the mechanical cooling equipment on board the ferry that sails around the region of Indonesia. Expected usage of this solar energy can reduce the use of fossil fuels oil and can save on operational costs.